2017
DOI: 10.1186/s12974-016-0774-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral ischemic damage in diabetes: an inflammatory perspective

Abstract: Stroke is one of the leading causes of death worldwide. A strong inflammatory response characterized by activation and release of cytokines, chemokines, adhesion molecules, and proteolytic enzymes contributes to brain damage following stroke. Stroke outcomes are worse among diabetics, resulting in increased mortality and disabilities. Diabetes involves chronic inflammation manifested by reactive oxygen species generation, expression of proinflammatory cytokines, and activation/expression of other inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
99
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 339 publications
(339 reference statements)
0
99
0
15
Order By: Relevance
“…Overwhelming epidemiological and clinical data have demonstrated that patients with DM are more sensitive to IRI . Diabetes and its associated hyperglycemia are involved in a variety of ischemic tissue injuries, including in the lungs, brain, kidney, and liver . The numerous functions of S1P include the regulation of cell death, proliferation, motility, differentiation, and inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overwhelming epidemiological and clinical data have demonstrated that patients with DM are more sensitive to IRI . Diabetes and its associated hyperglycemia are involved in a variety of ischemic tissue injuries, including in the lungs, brain, kidney, and liver . The numerous functions of S1P include the regulation of cell death, proliferation, motility, differentiation, and inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…(28) Diabetes and its associated hyperglycemia are involved in a variety of ischemic tissue injuries, including in the lungs, brain, kidney, and liver. (29)(30)(31)(32) The numerous functions of S1P include the regulation of cell death, proliferation, motility, differentiation, and inf lammation. (33)(34)(35) Most of the effects of S1P are mediated through the S1PR family, which includes the ubiquitously expressed S1PR1, S1PR2, and S1PR3 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanisms of hyperglycemia induce oxidative stress; promote formation of advanced glycosylation end products; 40,41 increase blood–brain barrier permeability and inflammatory responses; 42 lead to accumulation of reactive oxygen species/reactive nitrogen, inflammation, and mitochondrial dysfunction; 43 lead to cellular dysfunction; damage vascular tissue; inhibit endogenous vascular protective factors; alter vascular homeostasis; 44 raise levels of reactive oxygen species and advanced glycation end products; decrease levels of mitochondrial superoxide dismutase; 41 and correlate with endothelial cell dysfunction and nitric oxide production. 45 All these actions contribute to accelerating the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9]. Besides, a series of damage mechanisms such as glial cell activation, increased or decreased neurotransmitters, activation of oxidative stress, and neuro immunization which all play a critical role in the development of Bins-wanger disease, Alzheimer's disease (AD), Vascular dementia (VD) and so on, are involved under chronic cerebral ischemia [10][11]. Microglia of neuroprotective and neurotoxic properties are now generally considered as immunological cells widely distributed in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%